Manejo optométrico post cirugía de catarata senil paciente femenino de 60 años de edad. - Duarte Bravo, Génesis Elizabeth (2022)
The clinical case is about a 60 years old female patient, who had a surgical intervention due to a pathology called cataracts, they used the phacoemulsificacion method to extract the cataracts. She was fitted with monofocal intraocular lenses to see far away. Cataracts are based on the loss of transparency of the crystalline lens, the only way to cure it is by means of an ocular surgery. After the surgery the patient went for a visual examination, since she presented intermediate and near visual decrease. So, we recommended progressive occupational anti-reflective progressive lenses, the patient opted for the lenses. Trough this treatment using the lenses, the patient will be able to enjoy a better visual quality. The progressive lenses that the patient opted for must be worn permanently .